2012
DOI: 10.17795/jjnpp-4067
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cell Compatibility and Elastic Modulus of Silicone Rubber/Organoclay Nanobiocomposites

Abstract: Background: Substrates in medical science are hydrophilic polymers undergoing volume expansion when exposed to culture medium that influenced on cell attachment. Although crosslinking by chemical agents could reduce water uptake and promote mechanical properties, these networks would release crosslinking agents. In order to overcome this weakness, silicone rubber is used and reinforced by nanoclay. Objectives: Attempts have been made to prepare nanocomposites based on medical grade HTV silicone rubber (SR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…Our results coincide with the observations reported by Rowlands et al (2008), who found that over a certain Young's modulus value materials' elasticity does not affect MSC proliferation. Hosseini et al (2012) also obtained similar results for endothelial cells when cultured on polydimethylsiloxane/nanocilica composites with different NP concentrations. However, it must be highlighted that the authors used materials with much lower range of elasticity, in kPa and MPa scale, as well as different cell types.…”
Section: Discussionsupporting
confidence: 66%
“…Our results coincide with the observations reported by Rowlands et al (2008), who found that over a certain Young's modulus value materials' elasticity does not affect MSC proliferation. Hosseini et al (2012) also obtained similar results for endothelial cells when cultured on polydimethylsiloxane/nanocilica composites with different NP concentrations. However, it must be highlighted that the authors used materials with much lower range of elasticity, in kPa and MPa scale, as well as different cell types.…”
Section: Discussionsupporting
confidence: 66%
“…A clay − silver nanohybrid (AgOM) embedded hyperbranched epoxy could be a good platform for this purpose. Hosseini et al utilized an organophilic nanoclay in rubber and witnessed enhanced cell behavior . This was attributed to the porous structure of the nanoclay surface which helps the cells to adhere and grow.…”
Section: Introductionmentioning
confidence: 99%